Penerapan Metode Pembelajaran Case Studies dalam Meningkatkan Hasil Belajar Siswa Materi Sifat-Sifat Allah SWT - Yusmaneli Yusmaneli (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
The learning process that occurs in schools is that students only get material from the teacher after it is finished. One of them is the case studies learning method. The purpose of this research is to improve student learning outcomes in the material attributes of Allah SWT through the application of the case studies learning method in class VII B MTsN 1 Kerinci. Based on the Aqidah Akhlak test scores, there were 10 students with poor grades, 6 students with moderate scores, 3 students with good grades and 1 student with excellent grades. Based on cycle 1, there were 4 students with low scores, 8 students with moderate scores, 6 students with good scores and 2 students with very good grades. This shows that the learning outcomes of Aqidah Akhlak have not reached 50% of students whose learning outcomes are above the value/number 70, so that action is needed in cycle 2. Based on cycle 2 there were 10 students with sufficient scores, 5 students with good grades and 5 students very good students. This shows that the learning outcomes in this study have reached 50% of students whose learning outcomes are above the value/number 70, so there is no need for further action. The final conclusion in this study, the case studies learning method can improve learning outcomes Aqeedah morals, especially material about the Attributes of Allah SWT for students of class VII B MTsN 1 Kerinci.